Fodder Yield and Quality of Pearl Millet (Pennisetum glaucum L.) Genotypes as Influenced by Salinity of Irrigation Water in North Western India - Makarana, Govind; Yadav, R. K.; Kumar, Rakesh; Soni, P. G.; Yadav, Taramani; Yadav, M. R.; Datt, Chander; Rathore, D. K.; Kar, Suraj; Meena, V. K. (Indian Journal of Animal Nutrition, 2017)
The present study was undertaken to assess the effect of irrigation water salinity and verieties on forage yield and quality of pearl millet in north western India. The experiment was conducted with four main-plot treatments consisting of levels of saline irrigation water i.e. normal ( 0.6 dS/m) and 3, 6 and 9 dS/m irrigation water and two sub-plot treatments of pearl millet varieties i.e. AVKB-19 and ICMV-15111. The minimum DM content (15.71 and 16.68%), maximum CP content (9.26 and 7.48%) and (EE) (2.36 and 1.81%) was recorded at 1st cut and 2nd cut, respectively under good quality water. Among the genotypes, at 1st and 2nd cut, the maximum DM content (17.57 and 20.19%) was recorded in cv. ICMV-15111 compared to AVKB-19 (16.47 and 17.36%). In contrast, AVKB-19 recorded higher CP and EE level than ICMV-15111. Application of good quality water increased the DM yield by 23.34 and 13.69% and CP yield by 46.0 and 22.0% over irrigation water of EC 9.0 dS/m at 1st and 2nd cut, respectively. The cv. AVKB-19 gave higher DM (5.67 and 5.09 t/ha) and CP yield (1.42 and 1.25 q/ha) at the 1st and 2nd cut, respectively over ICMV-15111. The cv. AVKB-19 also recorded higher EE yield than ICMV-15111 at 1st cut while the reverse trend was observed at 2nd cut where ICMV-15111 which showed higher (P=0.05) EE yield over AVKB-19. The maximum NDF (66.35 and 70.64 %) and ADF (36.50 and 39.89%) content was recorded with EC 9.0 dS/m at 1st and 2nd cut, respectively. The highest carbohydrate content was recorded with 9.0 dS/m EC water irrigation for 1st and 2nd cuts. Therefore, ABKV-19 genotype of pearl millet proved to be superior and might be adapted for getting higher fodder yield with better quality as compare to the ICMV 15111 under saline environment in north-western region of India.